Snakebite envenoming in Brazilian children: clinical aspects, management and outcomes. (16th February 2023) - Oliveira, Isadora S; Pucca, Manuela B; Cerni, Felipe A; Vieira, Samuel; Sachett, Jacqueline; Seabra de Farias, Altair; Lacerda, Marcus; Murta, Felipe; Baia-da-Silva, Djane; Rocha, Thiago Augusto Hernandes; Silva, Lincoln Luís; Bassat, Quique; et al.
Abstract: Snakebite envenoming is currently considered a neglected tropical disease, which affects over 5 million people worldwide, and causes almost 150 000 deaths every year, as well as severe injuries, amputations and other sequelae. Snakebite envenoming in children, although proportionally less frequent, is generally more severe, and represents an important challenge for pediatric medicine, since they often result in worse outcomes. In Brazil, given its ecological, geographic and socioeconomic characteristics, snakebites are considered an important health problem, presenting approximately 30 000 victims per year, approximately 15% of them in children. Even with low snakebite incidence, children tend to have higher snakebite severity and complications due to the small body mass and same venom volume inoculated in comparison to adults, even though, due to the lack of epidemiological information about pediatric snakebites and induced injuries, it is difficult to measure the treatment effectiveness, outcomes and quality of emergency medical services for snakebites in children. In this review, we report how Brazilian children are affected by snakebites, describing the characteristics of this affected population, clinical aspects, management, outcomes and main challenges.